The Eternal Evergreen of Statutory Inheritance Law – Branch Inheritance from a Legal-Historical and Linguistic Point of View in the Law Valid in Slovakia until 1950 - Adriana Švecová; Peter Gergel (Journal on European History of Law)
The study will present the legal basis of the institution of branch inheritance and its primary problems in the application (judicial) practice of Hungarian dualism and I. Czechoslovak Republic. It will also look at the de lege ferenda proposals – Teleszky’s 1882 draft law of inheritance, reworked into the government’s 1887 draft law of inheritance, the 1900 draft of the 1st Hungarian General Civil Code, and the government’s 1933 to 1937 draft laws on branch succession. The draft Czechoslovak legislation was intended only as a temporary solution to the special (sui generis) legal inheritance of inherited property for the inheritance law in force in Slovakia and Subcarpathian Rus. The then Hungarian and Czechoslovak legal scholarship and practice, when repeatedly considering branch inheritance, was based on its acceptable preservation and therefore until the adoption of the first socialist Civil Code (1950) branch inheritance remained a part of the bourgeois inheritance law in Slovakia.